PENGARUH DIUNDANGKANNYA UNDANG UNDANG NOMOR 2 TAHUN 1960 TENTANG PERJANJIAN BAGI HASIL TERHADAP PELAKSANAAN BAGI HASIL TANAH PERTANIAN DI DESA NANGGULAN KECAMATAN CAWAS KABUPATEN KLATEN - Prasetyo, Agung Basuki (Diponegoro Private Law Review, 2017)
The enactment of Law number 2 year 1960 on Production Sharing Agreement does not affect the implementation of agricultural product sharing in Nanggulan Village, Kecamatan Cawas, KlatenDistricts. Indonesia whose majority of the population as farmers, but not all have their own farmland. So it is possible to establish a working relationship between the landowner and the farm workers. In order to protect vulnerable farm workers from being treated unfairly, the Government issued Law number 2 year 1960 on Production Sharing Agreement. In fact, the implementation of the agreement for the production of agricultural land in Nanggulan Village still uses the customary law, orally, the term of the agreement and the amount of the balance depending on the agreement of the landowner and farm workers.While the factors that led to the agricultural product sharing  that still use customary law, is in addition to the lack of public knowledge of Law Number 2 year 1960, also the strength of the principle of trust, and please help the lives of local communities.Key words: Production Sharing Agreement, Farmland